Phenotype Characterization of Beta-Lactamase Producing Enterobacteriaceae in the Intensive Care Unit (ICU) of Cipto Mangunkusumo Hospital in 2011 - Yulia R Saharman; Delly C Lestari (Acta Medica Indonesiana)
Aim: the goal of this study is to understand the phenotype characteristic of beta-lactamase enzymes producing Enterobacteriaceae, such as ESBL, AmpC, and carbapenemase. Methods: three different methods are performed to confirm those phenotypic characteristics, namely double disk diffusion method to confirm ESBL, AmpC disk test (cefoxitin-based) to confirm AmpC, and modified Hodge test to confirm carbapenemase. Results: using double disk diffusion method, we found 58.42% isolates are ESBL-producing, whereas the outcomes of AmpC disk test shows 1.98% are AmpC-producing. By conducting modified Hodge test (MHT), 27.59% isolates are confirmed as carbapenemase-producing bacteria. Conclusion: this study confirmed the prevalence of beta-lactamase producing Klebsiella pneumoniae is very high. Nevertheless, AmpC and carbapenemase should not be ignored despite their low prevalence.